Mikolay Petrovich Novachenko — large seen from a distance (1898–1966 years) - Korzh, Mykola; Shevchenko, Stanislav (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2017)
<span style="font-size: 14.0pt; mso-bidi-font-size: 9.0pt; font-family: ’Times New Roman’; mso-fareast-font-family: ’Times New Roman’; color: #221e1f; mso-ansi-language: RU; mso-fareast-language: RU; mso-bidi-language: AR-SA; mso-bidi-font-style: italic;">The article briefly describes the scientific and pedagogical way of the great organizer, scientist, brilliant teacher, talented doctor, corresponding member of the Academy of Medical Sciences of the USSR, honored worker of science of Ukraine, doctor of medical sciences, professor Novachenko Nikolai Petrovich, the director of the Scientific research institute of orthopedics and traumatology named by M. I. Sytenko, head of the department of orthopedics and traumatology of the Ukrainian institute of postgraduate education, editor-in-chief of the journal «Orthopaedics, traumatology and prosthetics». Born in a peasant family, he was educated at the church and parish schools in Sumy region, the gymnasium of Kharkov, and entered the medical faculty of Kharkov university, after which, in 1922, he began working at the Ukrainian institute of orthopedics and traumatology (now the «Sytenko Institute of Spine and Joint Pathology»). Having passed the way of the resident, the head of the radiology room and the clinical department, the chief physician of the institute, became its director. He was engaged in clinical practice and scientific research (in 1936 he defended his Candidate, and in 1940 — his doctoral dissertation). After demobilization in 1943 N. P. Novachenko devoted himself to the restoration of the institution and the education of cadres. Clinical works of N. P. Novachenko considers the topical issues of all sections of our specialty. His name is associated with: restoration and development of orthopaedic and traumatological and prosthetic services, organization of strong points, injuries treatment, development of functional techniques for the treatment of traumatic injuries; development of new reconstructive and restorative interventions on large joints with bone defects, preservation and transplantation of tissues (bones, tendons, skin), creation of tissue bank, restoration of the journal «Orthopaedics, traumatology and prosthetics» after the war.